Studies on the Active Components and Antioxidant Activity of the Extracts from Different Parts of Bamboo - Li, Yu-Xian; Cheng, Fang-Rong; Jin, Yong-Chun; Yuan, Ke (Asian Journal of Chemistry, 2013)
This work reports the determination of the total contents of flavonoids and phenolic acids in the extracted matter of the different parts in the bamboo (leaves, shoots and the bamboo shells) and on this basis, studied the free-radical scavenging function of the ethanol extracts for the total reducing power (TRP), Fe3+ reducing power (FRAP) and the reducing power of DPPH in the bamboo leaves, shoots and bamboo shells of the two different variants. The experimental results show that there are large amounts of flavonoids and phenolic acids in the bamboo leaves, shoots and bamboo shells. Through the research of antioxidation, it shows that the ethanol extracts of the bamboo leaves, shoots and bamboo shells of different variants all have strong free-radical scavenging power and the function of reducing Fe3+. By doing the relevant analysis for the contents and antioxidation power of the ethanol extracts of the different parts in bamboo, we know that there is strong correlation between the contents of flavonoids in the bamboo leaves, shoots and shells and the antioxidation power conducted by the determining system of DPPH and FRAP. There is also strong correlation between the total contents of phenolic acids and the antioxidation power determined by the system of TRP, DPPH and FRAP. It is concluded that Phyllostachys pubescens and Phyllostachys aureosuleata are the kind of bamboos which have strong antioxidant activity and thus provide scientific data for their further development and exploitation